Informed Consent: Good Medicine, Dangerous Side Effects - Waller, Bruce N. (Cambridge quarterly of healthcare ethics, 2008)
Informed consent has passed through three stages. The first paternalistic stage lasted for many centuries: The doctor's diagnosis and healing arts were kept secret, and informing patients was regarded as professionally and ethically wrong. Second came the legal stage, when the right of patients to make informed decisions concerning their own treatment was imposed by the courts and reluctantly tolerated by medical professionals. The third informed consent stage emerged more recently: the general therapy stage. The therapeutic benefits of informed consent have been well established, and informed consent is widely recognized as an important element in sound medical practice. When patients are effectively informed and can exert knowledgeable control over their own treatment decisions and therapy processes, that enhances recovery, strengthens the immune system, promotes better pain tolerance, prevents depression, and encourages patient cooperation and fortitude in treatment, rehabilitation, and preventative procedures. As the medical community has absorbed greater knowledge of this research, informed consent has been recognized as both ethically essential and therapeutically sound: the hallmark of the current general therapy stage of informed consent.